2015
DOI: 10.1016/j.ijscr.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Atypical localizations of calcific deposits in the shoulder

Abstract: HighlightsCase 1: massive calcific deposits in the context of the supraspinatus muscle belly.Case 2: calcific deposits at the biceps anchor.Case 3: calcific deposits in the cranial intra-articular trait of the subscapularis tendon.These 3 atypical cases were not responsive to conservative treatment.Arthroscopic removal of the deposits ensured an optimal clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…In Pereira's study, follow-up information was available in five subjects: two of which underwent arthroscopic surgery after the failure of conservative therapy [9]. Vinanti et al reported to have treated this disease surgically in one patient [11]; Wang et al treated one patient with an intramuscular calcification of the subscapularis through ultrasound guided needling [12]. In the case report presented by Mileto et al the patient was treated conservatively [10].…”
Section: Discussionmentioning
confidence: 99%
“…In Pereira's study, follow-up information was available in five subjects: two of which underwent arthroscopic surgery after the failure of conservative therapy [9]. Vinanti et al reported to have treated this disease surgically in one patient [11]; Wang et al treated one patient with an intramuscular calcification of the subscapularis through ultrasound guided needling [12]. In the case report presented by Mileto et al the patient was treated conservatively [10].…”
Section: Discussionmentioning
confidence: 99%
“…Rotator Cuff is the most affected site, in particular the supraspinatus tendon, followed by the infraspinatus, the subscapularis and the teres minor [11]. Despite its high prevalence in the rotator cuff, any tendon may be affected, with similar pathogenetic mechanisms and appearance.…”
Section: Upper Limbsmentioning
confidence: 99%
“…It has been described from case series and case reports as calcific opacities at plain radiographs or as inhomogeneous hyperechoic mass at US located along the anterior aspect of the proximal third of the biceps brachii muscle [ 66 , 67 ]. Calcifications at the origin of long head of the biceps, such as biceps anchor or biceps labral complex, have been less described in literature and generally present an ovoid shape, with their position close to the upper glenoid being unchanged during external or internal rotation of the humerus [ 66 , 68 , 69 ]. However, it is unlikely these represent real calcific tendinopathy but rather calcific apposition over degenerated tendons.…”
Section: Unusual Presentation Of Rcctmentioning
confidence: 99%